Невизначеність та відсутність арбітражної можливості - Ivanenko, Ya. V.; Pasichnichenko, I. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2014)
A new classification of the decision-making situations is proposed. It is based on the notion of uncertainty in matrix scheme of the situation. Such an approach to the classification of the decision-making situations differs from known approach, according to which the situations with risk and uncertainty are distinguished depending on the presence of probability distribution on the values of an unknown parameter. The necessary and sufficient conditions for existence of uncertainty in matrix scheme are established. The proposed notion of uncertainty is applied to the analysis of the financial markets. It is shown that the absence of an arbitrage opportunity on the financial market in the Arrow–Debreu model with a riskless asset is a particular case of the existence of uncertainty in the decision-making situation. This result gives an opportunity to view the no–arbitrage pricing theory for financial instruments as a branch of the general decision theory.